2019
DOI: 10.1128/mbio.00152-19
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Human Papillomavirus E1 Helicase with UAF1-USP1 Promotes Unidirectional Theta Replication of Viral Genomes

Abstract: Human papillomaviruses (HPVs) are important pathogens with a significant medical burden. HPV genomes replicate in infected cells via bidirectional theta replication and a poorly understood unidirectional mechanism. In this report, we provide evidence that the previously described interaction between the viral E1 helicase and the cellular UAF1-USP1 deubiquitinating enzyme complex, a member of the Fanconi anemia DNA damage response pathway, is required for the completion of the bidirectional theta replication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…In addition, TOP2b or other topoisomerases may play a critical role in helping resolve concatemeric viral genomes resulting from amplification. Amplification has been reported to occur through several potential mechanisms, including a rolling circle type process or a novel unidirectional replication scheme involving multiple initiation sites (21,22). It is also possible that amplification occurs though bidirectional theta structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TOP2b or other topoisomerases may play a critical role in helping resolve concatemeric viral genomes resulting from amplification. Amplification has been reported to occur through several potential mechanisms, including a rolling circle type process or a novel unidirectional replication scheme involving multiple initiation sites (21,22). It is also possible that amplification occurs though bidirectional theta structures.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes were induced to differentiate through a calciummediated switch (3). Briefly, keratinocytes were plated at 5 million cells per 10-cm dish in M154 keratinocyte medium (Thermo Fisher) containing 0.07 mM Ca 21 and human keratinocyte growth serum (HKGS; Thermo Fisher). The next day, the medium was changed to 0.03 mM Ca 21 in M154 containing HKGS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, TOP2 or other topoisomerases may play a critical role in helping resolve concatemeric viral genomes resulting from amplification. Amplification has been reported to occur through several potential mechanisms including a rolling circle type process or a novel unidirectional replication scheme involving multiple initiation sites (22,23). It also is possible that amplification occurs though bi-directional theta structures.…”
mentioning
confidence: 99%
“…The question of whether the maintenance replication of the HPV genome is under the control of the cellular origin licensing machinery and restricted to one replication per cell cycle, or whether replication is statistically completed once per cell cycle, has remained obscure, since both options have been proposed (8,9). Second, it has been shown that a novel mode of replication is initiated already during the transient replication of the viral genome, as determined by two-dimensional (2D) gel electrophoresis analysis of replication intermediates (10,11). The exact nature of this novel mode of replication has remained enigmatic, but it has been suggested to involve cellular recombination-dependent replication machinery (10).…”
mentioning
confidence: 99%